(untitled) (Kronika Bydgoska, 2016)
In spring of 1939, in May, when the threat of the outbreak of the war was becoming more real, Polish newspapers were printing names of people who were ready to sacrifice their lives defending the Homeland, enrolling themselves as candidates to serve as “live torpedoes.” For about a month, volunteers from Bydgoszcz and its environs were reporting themselves to the daily “Dziennik Bydgoski.” According to estimates, altogether 5,000 people, including males and females, young and old, retired military men, workers and unemployed were able to give their lives for Poland. About a hundred people from Bydgoszcz, known by name, reported for such service. This readiness had not been used in any way by the command of the Navy. Such plans had never existed and also were not developed in 1939.